Journal of Instrumentation - Dik, A. V. (2018)
In this paper the effective potential describing interaction of a scalar quantum particle with arbitrary nonuniform laser field is derived for a wide spectrum of the particle energies. The presented method allows to take into account all the features of the effective potential for a scalar particle. The derived expression for effective potential for quantum particle has the same form as the one presented earlier for a classical particle. A special case for channeling of a quantum particle as well as accompanying channeling radiation in a field formed by two crossed plane laser waves is considered. It is shown that relativistic particles moving near the laser channel bottom should be examined as quantum ones at both arbitrarily large longitudinal energies and laser fields of accessible intensities.